Estudo de variáveis organizacionais e psicológicas relacionadas a acidentes de trabalho em uma indústria de construção naval - Dela Coleta, José Augusto (1975)
The aim of this thesis is to the parameters of organizat1onal and explore psychosocial variables, associated with the accidents of a Navy Construct1on Industry in Rio de Janeiro State by the utilization of rnathemat1cal models based on 'Queueing Theory'. The first part is about a review of the principal researches and studies relating several psycholog1cal social, physiological physical and sociological, organizational variables at the events of accidents which occured in a Navy Construction Industry (1974), when the parameters which rule the distribution of the number of accidents suffered per workers and the intervals between successive accidents were evidenced. It is still considered the equations which should be employed for the prevision of the two dependent variables considered. Finally some suggestions and conclusions are shawn the most important one refers to the invariance of the parameters when different personal characteristics are considered. This is expla1ned by considering that the grade of danger is very high and should leave out the influences of the personal variables at the occurrence of work accidents.